Age Diversity Management in Organizations Scale: Development and Evidence of Validity - Seidl,Juliana (2022)
Abstract This study aimed to develop the Age Diversity Management in Organizations scale for the Brazilian context and verify its evidence of validity. The process included five steps: proposal of its definition and development of the items according to the literature; content and semantic validity by judges; semantic validity by the target population; exploratory factorial analysis (EFA); and confirmatory factorial analysis (CFA). The EFA sample consisted of 674 workers from different organizations and the CFA of 722 workers. The final version of the scale was composed of 20 items (α =.91), divided into four factors: retirement preparation practices (5 items, α =.93); equal treatment for workers of different ages (6 items, a=.85), training to promote age diversity (5 items, α =.81), and management practices for older workers (4 items, α =.72). The theoretical and practical implications as well as the limitations of this measure are discussed.